Implementasi Restorative Justice Untuk Menanggulangi Kekerasan Dalam Rumah Tangga: Antara Konsep dan Praktik - Aminah, Siti; Rafsanjani, Ony (Federation of Indonesian Probation Officer, 2023)
Abstract. Domestic violence is a common thing experienced by everyone, whether they realize it or not. Domestic violence is commonly manifested as physical violence, which results in physical injuries to the victims, the majority of women and children. The effects include injuries, psychological disorders, disability, and even death. Restorative justice brings a new dynamic for both parties involved in domestic violence cases, where the resolution of the criminal cases does not have to be achieved through a trial in court, which is expensive, time- and resource-consuming, and most importantly, provides no room and opportunity for the perpetrator to amend their mistakes. This research uses normative research methods, where we collect legal sources and materials from literature, books, reports, laws, and journals to expert opinions, which are then analyzed to solve the problems being discussed. The finding of the study shows that restorative justice is strongly oriented towards fulfillment of the victims’ rights, restoring the victims’ mental condition, and helping the perpetrator take responsibility for all the damages suffered by the victim. However, in its implementation, while restorative justice was expected to be pro-victim, it instead turned into a legitimizing tool for perpetrators to avoid criminal punishment as stated in Law number 23 of 2004 concerning the Eradication of Domestic Violence. In implementing the main principles of restorative justice, human resources with adequate competence regarding knowledge, understanding and ability in terms of implementing restorative justice mechanisms is required. Furthermore, law enforcement officers and the public must also be educated about gender justice and a culture of equality to minimize the repetition of similar cases. Keywords: Domestic violence, Law 23/2004, restorative justice Abstrak. Kekerasan dalam rumah tangga merupakan hal biasa yang dialami oleh semua orang, baik disadari maupun tidak. Kekerasan dalam rumah tangga banyak terjadi dalam bentuk kekerasan fisik, yang mengakibatkan di antaranya luka-luka pada fisik korban, yang sebagian besar merupakan perempuan dan anak. Efek yang ditimbulkan meliputi luka-luka, gangguan psikologis, kecacatan, hingga kematian. Hadirnya restorative justice membawa angin segar bagi kedua belah pihak yang terlibat dalam kasus kekerasan dalam rumah tangga, dimana dalam menyelesaikan permasalahan tidak harus dengan meja hijau, selain karena mahal, waktu, dan tenaga juga ikut terkuras, dan yang paling penting, tidak ada ruang bagi pelaku dalam memperbaiki kesalahannnya. Penelitian ini menggunakan metode penelitian bersifat normatif, yaitu mengumpulkan sumber dan materi hukum dari literatur, buku, laporan, undang-undang, jurnal, hingga pendapat ahli yang dilakukan analisa dalam menyelesaikan masalah yang dibahas. Hasil penelitian menunjukkan bahwa restorative justive sangat berorientasi pada pemenuhan hak korban, pemulihan kondisi mental korban, dan membantu pelaku bertanggung jawab atas segala kerugian yang diderita korban. Namun, dalam implementasi di lapangan, restorative justice yang diharapkan pro korban, malah berbalik menjadi alat legitimasi bagi pelaku untuk menghindar dari hukuman pidana sebagaimana yang tercantum dalam Undang-Undang nomor 23 tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga. Untuk mewujudkan prinsip utama restorative justice, maka diperlukan sumber daya manusia yang kapasitasnya mumpuni terkait pengetahuan, pemahaman, dan kemampuan dalam hal penerapan mekanisme keadilan restoratif. Selain itu, para aparat penegak hukum dan masyarakat juga perlu diedukasi tentang keadilan gender dan budaya kesetaraan untuk meminimalisir pengulangan kasus serupa. Keywords: kekerasan dalam rumah tangga, restorative justice, UU PKDRT